Methylglyoxal-Dependent Glycative Stress Is Prevented by the Natural Antioxidant Oleuropein in Human Dental Pulp Stem Cells through Nrf2/Glo1 Pathway - Simona Delle Monache; Fanny Pulcini; Roberta Frosini; Vincenzo Mattei; Vincenzo Nicola Talesa; Cinzia Antognelli (MDPI AG, 2021)
Methylglyoxal (MG) is a potent precursor of glycative stress (abnormal accumulation of advanced glycation end products, AGEs), a relevant condition underpinning the etiology of several diseases, including those of the oral cave. At present, synthetic agents able to trap MG are known; however, they have never been approved for clinical use because of their severe side effects. Hence, the search of bioactive natural scavengers remains a sector of strong research interest. Here, we investigated whether and how oleuropein (OP), the major bioactive component of olive leaf, was able to prevent MG-dependent glycative stress in human dental pulp stem cells (DPSCs). The cells were exposed to OP at 50 µM for 24 h prior to the administration of MG at 300 µM for additional 24 h. We found that OP prevented MG-induced glycative stress and DPSCs impairment by restoring the activity of Glyoxalase 1 (Glo1), the major detoxifying enzyme of MG, in a mechanism involving the redox-sensitive transcription factor Nrf2. Our results suggest that OP holds great promise for the development of preventive strategies for MG-derived AGEs-associated oral diseases and open new paths in research concerning additional studies on the protective potential of this secoiridoid.